The influence of the caruncle on the germination of castor seed under high salinity or low soil water content - Severino, L. S.; Cordoba G, O. J.; Zanotto, Maurício Dutra [UNESP]; Auld, D. L. (Ista-int Seed Testing Assoc, 2012)
The caruncle is a structure present in the micropylar region of Euphorbiaceae seeds. This structure has the ecological function of promoting seed dispersal by ants (myrmecochory), but it is debated whether it also has an agronomical importance influencing seed germination. The influence of the caruncle on castor (Ricinus communis) seed germination was evaluated under low soil water content and high soil salinity. Seeds were germinated at soil water storage capacities varying from 22 to 50% and salinities (NaCl) varying from 0 to 10 dS m(-1) The germination (%) increased following the increments in soil moisture. hut the caruncle had no influence on this process at any moisture level. In one genotype. more root dry mass was produced when caruncle was excised. Increasing salinity reduced the percentage and speed of germination of castor seeds, but no influence of caruncle was detected. No evidence of caruncle influencing castor seed germination was found under low soil water content and high salinity.